PATTERNS OF DELIVERING TA'ARUF HADITH IN DIGITAL DA'WAH: ANALYSIS OF STRATEGIES AND AUDIENCE INFLUENCE ON YOUTUBE LECTURES - Qonitah Hadi Winarko (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2025)
The phenomenon of ta’aruf (getting to know a prospective spouse before marriage) as an Islamic alternative to dating has become increasingly popular in the digital era, particularly through da’wah content on YouTube. This study is guided by three main questions: how are hadiths on ta’aruf delivered by preachers, how does the audience influence their delivery strategies, and how do variations in style affect the understanding of the da’wah message. The method used is qualitative content analysis by examining four sermons from Ustadz Muhammad Nuzul Dzikri, Ustadz Khalid Basalamah, Ustadz Faqih Abdul Kadir, and Ustadz Syafiq Riza Basalamah. The findings indicate that each preacher adapts their style, format, and language to the characteristics of the intended audience: Nuzul Dzikri employs a relaxed and communicative style with light humor, Khalid Basalamah uses a visual podcast format with a direct and applicative approach, Faqih Abdul Kadir presents an academic and contextual analysis, while Syafiq Riza Basalamah combines a formal-popular style with emotional emphasis. This study contributes to contemporary hadith scholarship by affirming that digital da’wah strategies not only convey normative texts but also build connections with audiences through diverse forms of communication. The conclusion underscores that despite differences in methods, the core message remains consistent: the importance of ta’aruf as a sharia-compliant alternative in building an Islamic marriage. However, the limitation of this study iles in its restricted scope of preachers and media platforms, which calls for further research to broaden the context and examine the real impact of audience reception.